Life cycle assessment of an Australian higher education institution – The case study of the Queensland university of technology - Kristina Schmidt; Meret Jürgens; Hans-Josef Endres; Sebastian Spierling; Leonie Barner (Cleaner Environmental Systems)
The environmental impact of the operation of an Australian University, i.e. the Queensland University of Technology (QUT), in 2022 has been assessed by applying the recently published life cycle assessment guidelines for Higher Education Institutions. Overall, 16 environmental impact categories were considered based on ISO 14072. QUT's energy supply was identified as the most substantial impact overall, accounting for over 48 % in each of eight impact categories. Airconditioning (with the use of the refrigerant R134a) has the highest impact on the ozone depletion category. Transport exhibits the second most significant impact in eight of the 16 impact categories, mostly due to international air travel by international students and staff. Infrastructure has the most significant impact in six categories but is probably underestimated due to lack of data. In addition, suggestions how to reduce QUT's environmental impact are discussed. Subsequently, recommendations to develop the LCA guidelines for HEIs further are presented.